Accounting: A Programmed Text (Book). - Sterling, Robert R.; Montgomery, James B. (The Accounting Review, 1971)
Reviews the book "Accounting: A Programmed Text," vol. 2, by James Don Edwards, Roger H. Hermanson and R.F. Salmonson.